Analisis Kesenjangan Antara Pengetahuan dan Keterampilan Menulis Narasi Peserta Didik Kelas IV Sekolah Dasar - Selvi Selvi; Chandra Chandra; Salmaini Safitri Syam (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The purpose of the research was to analyze the gap between students' narrative writing knowledge and skills. This research employs a qualitative methodology, specifically descriptive qualitative research. Data is gathered using document study methods, which include gathering and examining written documents, photographs, artwork, and electronic devices. A systematic study is then created by analyzing, comparing, and synthesizing the collected documents. Based on the aforementioned data collection methods, the research tools used are the narrative text knowledge assessment sheet and the narrative text writing skills assessment sheet. It is possible to draw the conclusion that students' knowledge and proficiency in the narrative text material are lacking.